DOP12 Validation of a modified simple ultrasound activity Score for children with Crohn's Disease. (27th May 2021) - Ma, H; Isaac, D M; Petrova, A; Almeida, P; Parsons, D; Kuc, A; Carroll, M W; Wine, E; Huynh, H
Abstract: Background: Transabdominal bowel ultrasound (TABUS) is an ideal tool to assess the bowel wall thickness (BWT) of children with Crohn's disease (CD) due to its minimal invasiveness. Recently the Simple Ultrasound Activity Score for CD (SUS-CD) was developed and validated in adults using the Simple Endoscopic Score for CD (SES-CD). Our aim was to determine how the SUS-CD performed in children at diagnosis in comparison to endoscopy. Methods: Pediatric patients (0–18 years old) with suspected inflammatory bowel disease (IBD) were prospectively enrolled through the Edmonton Pediatric IBD Clinic in Alberta, Canada. Patients underwent a baseline TABUS to visualize the intestine (excluding rectum, which is difficult to see with TABUS), blood work and endoscopy. The weighted pediatric CD activity index (wPCDAI) assessed disease activity, and SES-CD assessed endoscopic disease. Modified SUS-CD (excluding rectal sub score) was calculated using BWT scores (0=<3mm, 1=3–4.9mm, 2=5–7.9mm, 3=>8mm) and colour doppler scores (0=no or 1 vessel, 1=2–5 vessels, 2=>5 vessels per cm2) for each segment (terminal ileum, right colon, transverse colon, left colon) and compared to SES-CD. Modified SUS-CD was correlated to wPCDAI score, C-reactive protein (CRP) and fecal calprotectin (FCP). Using SPSS, anova and Chi square were used to assess for an association between TABUS parameters and wPCDAI. Spearman's rank (rho) and Pearson's correlation (r) were used to assess for a correlation between modified SUS-CD with SES-CD, wPCDAI, CRP and FCP. Results: 40 patients recruited, 35 had CD (mean age 12.6(2.85)) and 5 were normal and scanned for suspected IBD (mean age 12.2(3.75)). Median wPCDAI and SES-CD scores for CD patients were 61(IQR 35.6–77.5) and 15(IQR 7.5–21) respectively. Fat proliferation was associated with severe CD based on wPCDAI (p<0.05). The modified SUS-CD score correlated well with the modified SES-CD score (rho=0.79, r=0.76, p<0.001, R2 linear=0.465). When the BWT threshold was lowered by 0.5mm for each BWT category, correlation improved (rho=0.80, r=0.82, p<0.001, R2 Linear=0.541). Using a similar lower threshold for BWT, a receiver operating characteristic curve analysis revealed an area under the curve of 0.87 and 0.90 for detecting mild endoscopic activity and moderate endoscopic activity, respectively. There was a significant correlation between SUS-CD and wPCDAI score (r=0.56, p<0.01), CRP (r=0.55, p<0.01) and FCP (r=0.56, p<0.01). Conclusion: Fat proliferation was associated with more severe CD. The modified SUS-CD correlated well with modified SES-CD score, wPCDAI, CRP and FCP. Correlation improved when BWT threshold in each category was dropped by 0.5mm. These data support the use of TABUS as an effective adjunct to the assessment of pediatric CD.